Help-Seeking Behaviors for Intimate Partner Violence Perpetration by Men Receiving Substance Use Treatment: A Mixed-Methods Secondary Analysis - Hashimoto, Nozomu (Journal of interpersonal violence, 2021)
Despite the high prevalence of intimate partner violence (IPV) perpetration by men receiving substance use treatment, little is known about their help-seeking behaviors for IPV. A secondary analysis of a mixed-methods study of men receiving substance use treatment who perpetrated IPV examined the prevalence, characteristics, and barriers associated with IPV perpetration disclosure and help-seeking. In total, 170 men were interviewed using a structured questionnaire, and a subsample of 20 were interviewed in-depth about their experiences. Logistic regression determined variables associated with disclosure and help-seeking. Thematic analysis of the in-depth interviews explored barriers to disclosure and help-seeking. Only half the participants had told anyone about their IPV perpetration and about one quarter reported having sought any sort of support. Whereas participants were more likely to disclose their IPV perpetration to informal resources (such as friends or family), they tended to seek help from formal resources (such as health professionals or the police). A greater proportion of physical IPV perpetrators, who had disclosed, had been arrested or had police involvement for IPV, suggesting that their disclosure may not have been voluntary. The following themes emerged from the qualitative data about the barriers to disclosure and help-seeking for IPV perpetration: fear that their children would be taken into care by social services, shame and embarrassment, and a minimization or normalization of their behavior. In addition, many participants highlighted that they had never been previously asked about IPV during treatment for substance use and stressed the need for greater expertise in or knowledge of this topic from specialist services. Substance use treatment services should enquire about men’s relationships and IPV perpetration to facilitate disclosure and provide support. Further research is necessary to determine the context of disclosure and help-seeking for IPV perpetration to increase the likelihood of identification.